Diabetic Ketoacidosis in Northern Jordan: Seasonal Morbidity and Characteristics of Patients - Saadeh NA; Hammouri HM; Zahran DJ (Diabetes, Metabolic Syndrome and Obesity, 2023)
Nesreen A Saadeh,1 Hanan M Hammouri,2 Deeb J Zahran3 1Faculty of Medicine, Jordan University of Science and Technology, Irbid, Jordan; 2Department of Mathematics and Statistics, Jordan University of Science and Technology, Irbid, Jordan; 3St. James’s University Hospital, Infectious Diseases Department, Leeds, UKCorrespondence: Nesreen A Saadeh, Faculty of Medicine, Jordan University of Science and Technology, PO Box 3030, Irbid, 22110, Jordan, Email Nasaadeh@just.edu.joPurpose: This study aimed to characterize adult patients admitted with diabetic ketoacidosis (DKA) in northern Jordan.Methods: The study examined medical records of patients diagnosed with DKA from January 2015 to April 2018. Variables analyzed included diabetes type, precipitating illness, admission month, hospital length of stay, and biochemical markers.Results: Out of 232 admissions with DKA, 70% were diagnosed with type 2 diabetes, and 56% were females. 12% of admissions had a new diagnosis of diabetes, of which 51% had type 2 diabetes. Sepsis (48%), Non-adherence (26%), and diabetic foot infections (18%) were the most encountered precipitating factors for DKA in T1DM. As for T2DM, sepsis (52%), acute coronary syndrome (12%), and pancreatitis (8%) were the most precipitating factors for DKA. High urea levels, high creatinine levels, low phosphorous levels, low hemoglobin levels, and high platelet counts were associated with a longer hospital stay for type 1 diabetes. For type 2 diabetes, low pH on admission, old age, and high Hb A1c within 6 months of admission were factors associated with a prolonged hospital stay. The study found a significant peak of admissions for DKA in both type 1 and type 2 patients in the winter and spring months (Pearson P-value= 0.0013).Conclusion: The results of the present study highlight the seasonal variation in the frequency of DKA hospitalizations. It also highlights sepsis as the most frequent precipitating factor of DKA in both type 1 and type 2 DM patients.Keywords: diabetic ketoacidosis, Jordan, season, ketosis-prone diabetes